The Impact of Tank Disinfectants on the Development of Microbiota in Gilthead Seabream (Sparus aurata) Larviculture Systems - Georgia Apostolopoulou; Naima Bel Mokhtar; Elias Asimakis; Eva Dionyssopoulou; Kosmas Toskas; George Koumoundouros; George Tsiamis; Panagiota Stathopoulou (Microorganisms)
Aquaculture play a vital role in enhancing human nutrition by producing commercially valuable fish, with gilthead seabream (Sparus aurata) being a key species in the Mediterranean region. In seabream larviculture, disinfection is commonly used to control pathogens and prevent microbial imbalances. However, this process may also remove beneficial microbiota that contribute to ecosystem stability. This study aims to investigate the impact of tank disinfection operations on the bacterial communities associated with seabream larvae and their rearing water in a commercial hatchery using 16S rRNA amplicon sequencing. For further comparison, the bacterial communities present in eggs and feed were also analyzed for comparison. Results showed that the use of different disinfectants significantly altered the bacterial composition of the larvae, while the duration of the dry period had no measurable effect. Across all larval samples, the phylum Pseudomonadota dominated, with members of the genus Psychrobacter consistently detected regardless of disinfection treatment. This suggests that Psychrobacter may be transmitted from eggs or acquired through the feed, mainly rotifers and Artemia nauplii. In contrast, the bacterial communities in the rearing water were more diverse and showed only minor differences in relative abundance across disinfection methods.